Shadows of love, shadows of loneliness: volume 2 eaudiobook Drawings, prints & paintings: 1980-2020. - Vollmann, William T. (Shadows of Love, Shadows of Loneliness, 2022)
In this landmark collection, William T. Vollmann offers a kaleidoscopic retrospective of the visual artwork he has produced over four decades, with new commentary from Vollmann on his process, inspiration, and the many intersections with his writing. The celebrated author of over twenty-five books (among them the National Book Award-winning novel Europe Central; the seven-volume Rising Up and Rising Down, based on Vollmann's career as a war correspondent; and the two-volume climate change investigation Carbon Ideologies), Vollmann's equally ambitious and prolific career as a photographer, printmaker, and painter reflects the artist's deep interest in people existing on the margins, a profound empathy for his subjects, and the humility and generosity to meet them on their terms. In Shadows of Love, Shadows of Loneliness, a series of essays commissioned especially for this book lays out Vollmann's views on what photographs can and should say, how he chooses what to represent (beauty, suffering, compassion, love, desire, ideology), thoughts on photographic consensuality, and any number of technical descriptions. Particularly useful for Vollmann fans and scholars are the cross-references between these artistic and photographic projects and his books.